Implementation of the Qur'an Memorization Learning Curriculum for Al-Qudwah Primary School Students Malaysia - muhammad, irfan; Ruslan, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to overcome the implementation of the Qur'anic learning curriculum and identify supporting and inhibiting factors in the Qur'anic learning curriculum in al-Qudwah Malysia primary schools. This research was carried out using a qualitative research method, namely looking at the condition of natural objects and the researcher himself as an instrument by using the collection of obtained regulatory data and analysis of inductive or qualitative data. The results of the study show that the implementation of the Qur'an memorization learning curriculum has been carried out well so that students can implement it in their daily lives. With the learning of halarel, the Qur'an that has been applied in school makes students more noble, tawadhu', istqomah and stay away from reprehensible deeds.